Driving and Inhibiting Factors of Branchless Banking Technology Adoption in Rural Community - Franksiska, Rosaly; Purwati, Yenny; Nugroho, Paskah Ika; Widodo, Arief (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2017)
This research is aimed to understand the perception of rural people toward Branchless Banking and to explore the factors that encourage them to adopt Branchless Banking technology in Indonesian context.Â Innovation diffusion theory was used in this research. Variables consisted of relative advantage, compatibility, complexity, trialability, and observability used to explore the perception of rural people toward Branchless Banking.Â Questionnaires were distributed to people in Kuncen village, Salatiga Indonesia.Â We found that relative advantage and complexity are factors that drive Kuncen village people to adopt Branchless Banking. Thus, compatibility, trialability, and observability are the inhibitors for Branchless Banking adoption.Keywords: Branchless Banking, mobile payment systems, technology adoption, financial inclusion